MODEL OF SOCIAL AND ECONOMIC CHARACTERISTICS OF MSMEs IN UTILIZING ONLINE MEDIA TO INCREASE PEOPLE'SPOWER IN BATANG KUIS DISTRICT - Julita Julita; Nel Arianty; Rahmad Bahagia (RADJA PUBLIKA, 2021)
The purpose of the study was to determine and analyze the effect of Social Characteristics on Purchasing power, to find out and analyze the influence of MSME Economy on the Purchasing power, to find out and analyze the influence of online media on Purchasing power, to determine and analyze the influence, Social Characteristics, Economics of SMEs, and Online Media onPurchasing powerto the community in Batang Kuis District. The results showed that social characteristics had no significant effect on purchasing power. This shows the influence of the digital era that has been widely carried out in buying and selling interactions, so that direct social interaction is very rarely carried out. The MSME economy has a significant effect on purchasing power. This shows the influence of the community's economy that influences the purchase of a product. Online media has a significant effect on purchasing power. This shows the influence of social media which has been widely used by the community in carrying out activities including buying the necessary needs through social media.